Complications of antiretroviral therapy initiation in hospitalised patients with HIV-associated tuberculosis. - Helen van der Plas; Graeme Meintjes; Charlotte Schutz; Rene Goliath; Landon Myer; Dorothea Baatjie; Robert J Wilkinson; Gary Maartens; Marc Mendelson (PLoS ONE, 2013)
HIV-associated tuberculosis is a common coinfection in Sub-Saharan Africa, which causes high morbidity and mortality. A sub-set of HIV-associated tuberculosis patients require prolonged hospital admission, during which antiretroviral therapy initiation may be required. The aim of this study was to document the causes of clinical deterioration of hospitalised patients with HIV-associated tuberculosis starting antiretroviral therapy in order to inform healthcare practice in low- to middle-income countries.Prospective, observational cohort study of adult inpatients with HIV-associated tuberculosis starting antiretroviral therapy in a dedicated tuberculosis hospital in Cape Town, South Africa. Causes of clinical deterioration and outcome were recorded in the first 12 weeks of antiretroviral therapy. Patients with rifampicin-resistant tuberculosis were excluded.Between May 2009 and November 2010, 112 patients (60% female), with a median age of 32 years were enrolled. At baseline the median CD4 count was 55 cells/mm3 (IQR 31-106) and HIV viral load 5.6 log copies/mL. All patients had significant comorbidity: 82% were bed-bound, 65% had disseminated tuberculosis and 27% had central nervous system tuberculosis. Seventy six patients (68%) developed 144 clinical events after starting antiretroviral therapy. TB-IRIS, hospital-acquired infections and significant drug toxicities occurred in 42%, 20.5% and 15% of patients respectively. A new opportunistic disease occurred in 15% of patients and a thromboembolic event in 8%. Mortality during the 12 week period was 10.6%.High rates of TB-IRIS, hospital-acquired infections and drug toxicities complicate the course of patients with HIV-associated tuberculosis starting antiretroviral therapy in hospital. Despite the high morbidity, mortality was relatively low. Careful clinical management and adequate resources are needed in hospitalised HIV-TB patients in the 1(st) three months following ART initiation.